Le vocabulaire des lits de la Renaissance en France à la lumière des sources - Muriel Barbier (In Situ)
A few parts of some Renaissance beds have been preserved in France but not a single complete bed from the period starting in the middle of the fifteenth century and finishing at the beginning of the seventeenth has survived. Archival sources such as inventories after death, official reports, correspondence and contracts are consequently the only way of gaining some idea of what these beds looked like. But the terms used in these documents are far removed from present-day French. Based on archive documents (most of them already published) which primarily concern royal or princely interiors, this article proposes a decoding of the vocabulary pertaining to Renaissance beds. Beyond the polysemy of the word ‘bed’ itself, we look at the diversity of terms used to designate the bed frame, the textile elements and other elements constituting this piece of furniture for sleeping in.